Determinan of visitors consumption on sunday morning (sunmor) gor satria purwokerto - Sulistiawati, Dewi; Wibowo, Arif Andri (Enrichment : Journal of Management, 2024)
SUNMOR GOR Satria is a traditional market that only operates on Sundays, located in front of GOR Satria Purwokerto. Its strategic location and main road (Car Free Day) makes GOR busier than usual. This results in an increase in visitor consumption expenditure at Sunmor because the large number of goods traded can provide several choices for visitors to shop according to their wishes and needs. This research aims to analyze the influence of income, education level, age, travel distance and gender on visitor consumption expenditure. This research uses primary data totaling 100 respondents with a purposive sampling technique. The data analysis technique used is Multiple Linear Regression Analysis. The research results show that income, age and travel distance have a significant influence on visitor consumption expenditure at Sunmor GOR Satria Purwokerto. Meanwhile, education level and gender do not have a significant effect on consumption expenditure at Sunmor GOR Satria Purwokerto